1995
DOI: 10.1177/001440299506200105
|View full text |Cite
|
Sign up to set email alerts
|

Close to the Classroom is Close to the Bone: Coaching as a Means to Translate Research into Classroom Practice

Abstract: This study explored the use of coaching as a way to bring research-based teaching practices into general education classrooms to improve the quality of reading instruction provided to students with learning disabilities. Project staff trained and mentored district special educators on the process of coaching. Qualitative research methodology was used to analyze the process of expert consultation and to better understand the process of change. Key issues that emerged included differences in the ways that specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 23 publications
4
101
0
1
Order By: Relevance
“…During the process, the coach observed one-on-one conversations held by the teacher-researcher, providing immediate oral feedback. Studies conducted on the coaching approach have concluded that it is of tremendous importance that the process be based on real life practice so that the developmental needs of the teacher may be easily identified, so that the process may be managed at a balanced pace, and so that the desired development may be realized (Hunzicker, 2011;Gersten et al, 1995). Real practice is valued because it provides tangible examples to aid one in transferring and transforming knowledge into practice (Costa & Garmston, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the process, the coach observed one-on-one conversations held by the teacher-researcher, providing immediate oral feedback. Studies conducted on the coaching approach have concluded that it is of tremendous importance that the process be based on real life practice so that the developmental needs of the teacher may be easily identified, so that the process may be managed at a balanced pace, and so that the desired development may be realized (Hunzicker, 2011;Gersten et al, 1995). Real practice is valued because it provides tangible examples to aid one in transferring and transforming knowledge into practice (Costa & Garmston, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A closer look at the interaction between the teacher-researcher and the coach during the current study reveals that every step of the process was built on a number of quality interactions; namely, mutual respect, joint goals, joint decisions, and the equal opportunity to express their opinions. All of these features may be considered as factors that promote effective communication between teachers and coaches during professional development programs (Gersten et al, 1995;Irinaga-Bistolas et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Teacher Study Group (TSG) PD program used in this study was based on our earlier research efforts to identify strengths and weaknesses of PD strategies for translating research into teaching practice in high poverty schools (Gersten, Morvant, & Brengelman, 1995;Gersten & Brengelman, 1996;Gersten, Darch, Davis, & George, 1991;Gersten & Woodward, 1990) as well as principles gained from reviews of the PD literature. The TSG PD program was then defined and operationalized by senior research associates on the research team.…”
Section: Impact Of the Teacher Study Group 4 Teacher Study Groupmentioning
confidence: 99%
“…Or, parmi les savoirs qui peuvent aider à rendre les pratiques efficaces, se retrouvent des savoirs savants, issus de la recherche. Certains chercheurs assurent qu'il est crucial, particulièrement pour l'aide aux élèves en difficulté, que les enseignants adaptent leurs pratiques de diagnostic, d'intervention et d'évalua-tion à partir de ces savoirs vérifiables (Fuchs et Fuchs, 1998 ;Gersten, Morvant et Brengelman, 1995 ;Gersten et Brengelman, 1996 ;Gersten et al, 1997 ;Klingner et Hugues, 2003 ;Klingner, Vaughn, Hughes et Arguelles, 1999 ;Stanovich, 1994Stanovich, , 2000. Recourir à ces savoirs qui sont en évolution constante (Schulman, 1998 ;Wong, 1996) requiert cependant des habiletés spécifiques qui gagnent à être apprises lors de la formation initiale.…”
Section: Développement Professionnel Formation Et Rechercheunclassified